Clinical effects of acupuncture and periarticular local infiltration of corticosteroids in the treatment of gonarthrosis - Plavsic, Aleksandra; Brdareski, Zorica; Djurovic, Aleksandar (Acta Fisiátrica, 2006)
Gonarthrosis is one of the most frequently degenerative diseases. Pain, derange of function and= deformation of joint are dominating clinical signs. Aim of the study: To compare clinical effect obtained with three different therapeutic models: 1. Acupuncture; 2. Local infiltration of corticosteroid; 3. Combination of acupuncture and local infiltration of corticosteroid. Material and methods: An open, prospective, randomized clinical study included 21 female patients in acute phase of gonarthrosis. Diagnosis was made by clinical and radiographic examinations. Patients were divided into three groups: I group: 7 patients, average age 61.0 ± 6.8 years, treated with needle acupuncture (points: Du.20, Ex.31, Ex.32, St.35, UB.40, St.44, UB.60, Li.4, Sp.9,UB.11), 10 treatments. II group: 7 patients, average age 59.0 ± 10.1 years, treated with infiltration of Bethametasonum – Diprophos on the first day of treatment with frontal approach on the medial or the lateral side of m. quadriceps tendon. III group: 7 patients, average age 58 ± 6.07 years, treated with a combination of initial infiltration of Bethametasonum – Diprophos and needle acupuncture, 10 treatments. The evaluation of efficacy parameters were performed by following parameters: 1. Subjective difficulties – pain (VAS 0-100 mm); 2. Sizeof knee, measured across the middle of patella with centimeter band; 3. Range of joint motion (flexion), measured using a goniometer. All of these parameters were measured on 1st, 8th and 21st day of treatment. One way ANOVA, repeated measures ANOVA and post hoc tests were applied for statistic analysis. Results: 1. There were high significant improvements in the parameters of pain intensity and size of knee inside the groups; One way ANOVA test, p=0.000<0.01; 2. There were no significant improvements in the parameter of joint movement inside the groups; One way ANOVA test, p=0.528>0.05; 3. There were high significant improvements in all parameters (pain intensity, size of knee, joint movement) in all three groups; Repeated measures ANOVA test, p=0.000<0.01. Conclusion: Combined treatment of acupuncture and local infiltration of a corticosteroid has better effectiveness in pain intensity, size of knee and improvement of motion in comparison with monotherapy.